Pengaruh Instagram Terhadap Keputusan Berkunjung Wisatawan Milenial Di Pantai Pandawa, Bali - Desak Putu Rai Sattvika Putri; Dian Pramita Sugiarti (JURNAL DESTINASI PARIWISATA, 2021)
Pandawa Beach, one of the famous tourist attractions and visited by many tourists, is located in the southern part of Bali Island, precisely in Kutuh Village, Badung Regency, which offers a beautiful beach between solid cliffs and white sand. The tourist can also enjoy water attractions and culinary at beachside restaurants while enjoying the beach view. Pandawa Beach has turquoise water hidden behind sturdy limestone cliffs, stretching white sand and calm waves. This is an instagramable and worth sharing place on Instagram and is one of the factors for millennial tourists visiting Pandawa Beach. Therefore, millennial tourists who take photos on Pandawa Beach and upload them on Instagram will influence other millennials to visit Pandawa Beach. Based on these phenomena, the purpose of this study is to determine the influence of Instagram on millennial tourists decision to visit Pandawa Beach. The research method used is a quantitative approach. Data collection was carried out by means of a questionnaire, an observation, and a literature study. Data were analyzed with correlation analysis and hypotheses using the t test. The results of this study indicate that Instagram has a strong influence on millennial tourists decision to visit Pandawa Beach. Keywords: Influence, Instagram, Visit Decision, Millennial Tourists, Pandawa Beach